Synergy of Multimodal Literacy Approach and Role Playing Technique: A Quasi-Experiment on Reading Comprehension Skills in Elementary School - Afifah Istiqomah; Karmila J Umar; Karlina (Horizon of Primary Education, 2025)
Low reading comprehension skills and persistent student disengagement have emerged as critical global challenges, demanding innovative pedagogical solutions beyond conventional monomodal instruction. This study aimed to investigate the effectiveness of a multimodal literacy ecosystem integrated with role playing technique on improving reading comprehension skills of fourth-grade elementary school students. A quasi-experimental method with a Nonequivalent Control Group Pretest-Posttest Design was employed, involving 38 Grade IV students divided into an experimental class (n = 20) receiving multimodal role playing treatment and a control class (n = 18) following conventional text-based instruction. Data were collected through direct observation using structured rubrics measuring four cognitive indicators: literal comprehension and vocabulary, identifying main ideas, making inferences, and evaluating texts. Instrument validity was confirmed through expert judgment, with an inter-rater reliability coefficient exceeding 0.80. The Independent Sample t-test revealed a highly significant difference in learning outcomes (Sig. = 0.000 < 0.05), with a mean difference of 16.50 points. The experimental class achieved an N-Gain score of 0.88 (High Category), substantially outperforming the control class, which recorded 0.52 (Medium Category). The most pronounced gains were observed in higher-order thinking indicators, specifically inference making and text evaluation. These findings confirm that the multimodal role playing ecosystem effectively accelerates reading comprehension by enabling students to transform abstract textual meaning into kinesthetic and spatial experiences through collaborative transmediatory performance.